2000
DOI: 10.1016/s0146-6380(00)00085-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of high molecular weight biomarkers in crude oils

Abstract: High-temperature gas chromatography (HTGC) has enhanced our ability to characterize hydrocarbons extending to C 120 in crude oils. As a result, hydrocarbons in waxes (> C 20 ) have been observed to vary signi®cantly between crude oils, even those presumed to originate from the same source. Prior to this development, microcrystalline waxes containing hydrocarbons above C 40 were not characterized on a molecular level due to the analytical limitations of conventional gas chromatography. Routine screenings of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Hsieh and Philp measured HMWHCs from crude oils derived from different sources, including terrigenous, lacustrine, marine source material as well as source rock extracts. Different structural compositions of these HMWHCs (including alkyl-cycloalkanes, methylbranched alkanes, and alkyl-aromatic hydrocarbons) have been revealed by HTGC and it was found that the fraction of the HMWHCs in the whole oil is significantly higher than previously thought (can be up to 8%) (Hsieh & Philp, 2001;Hsieh et al, 2000). The distribution of long chain, branched and alkylcyclohexanes of the HMWHCs analyzed by HTGC has been used as a useful mean to distinguish oils derived from different sources (Huang et al, 2003).…”
Section: Wax Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Hsieh and Philp measured HMWHCs from crude oils derived from different sources, including terrigenous, lacustrine, marine source material as well as source rock extracts. Different structural compositions of these HMWHCs (including alkyl-cycloalkanes, methylbranched alkanes, and alkyl-aromatic hydrocarbons) have been revealed by HTGC and it was found that the fraction of the HMWHCs in the whole oil is significantly higher than previously thought (can be up to 8%) (Hsieh & Philp, 2001;Hsieh et al, 2000). The distribution of long chain, branched and alkylcyclohexanes of the HMWHCs analyzed by HTGC has been used as a useful mean to distinguish oils derived from different sources (Huang et al, 2003).…”
Section: Wax Analysismentioning
confidence: 97%
“…Other detection methods have also been used, including mass spectrometery (MS) (Hsieh et al, 2000;Philp, 1994), atomic emission detection (AED) (Asmussen & Stan, 1998) and inductively coupled plasma mass spectrometry (ICP-MS) (Glindemann et al, 2002), etc.…”
Section: Requirements On the Parts Of Htgcmentioning
confidence: 99%
“…The elevated abundance of NA with C n > 35 at some stations points to enhanced contribution of heavy fuel oil residuals (Brooks et al, 1954;Hsieh et al, 2000), while C n ≤ 23 NA without odd/even carbon preference (CPI 14−23 ∼ 1) likely derive from fossil inputs (light diesel, Wang et al, 1999) and/or reworked algal material (Saliot, 1981). However, the presence of the isoprenoid alkanes pristane (Pr) and phytane (Ph) along with the C n ≤ 23 NA in corresponding stations with a ratio Pr / Ph < 1 (Table 2) argues for a fossil origin of the C n ≤ 23 n-alkanes.…”
Section: Anthropogenic Sourcesmentioning
confidence: 99%
“…8 Understanding the heavy component of crude oil at the molecular level has been very important to improve petroleum processing. 9,10 Petroleomics refers to a research effort where detailed knowledge of heavy crude oil is pursued. 11,12 High resolution mass spectrometry especially Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) has been one of the key components for petroleomics.…”
Section: Introductionmentioning
confidence: 99%